2017
DOI: 10.1016/j.ynstr.2016.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Early life adversity: Lasting consequences for emotional learning

Abstract: The early postnatal period is a highly sensitive time period for the developing brain, both in humans and rodents. During this time window, exposure to adverse experiences can lastingly impact cognitive and emotional development. In this review, we briefly discuss human and rodent studies investigating how exposure to adverse early life conditions – mainly related to quality of parental care - affects brain activity, brain structure, cognition and emotional responses later in life. We discuss the evidence that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
80
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(83 citation statements)
references
References 133 publications
0
80
0
3
Order By: Relevance
“…While hippocampal dependent learning and memory processes are generally hampered, LBN in fact enhances contextual aspects of conditioned fear as described above (Arp, et al, 2016; Krugers, et al, 2016). In particular, LBN reduces the ability to discriminate between tone-on and tone-off periods in an auditory fear-conditioning paradigm (Arp, et al, 2016).…”
Section: Proximal (Neonatal) and Distal (Adult) Phenotypes Resultimentioning
confidence: 94%
See 2 more Smart Citations
“…While hippocampal dependent learning and memory processes are generally hampered, LBN in fact enhances contextual aspects of conditioned fear as described above (Arp, et al, 2016; Krugers, et al, 2016). In particular, LBN reduces the ability to discriminate between tone-on and tone-off periods in an auditory fear-conditioning paradigm (Arp, et al, 2016).…”
Section: Proximal (Neonatal) and Distal (Adult) Phenotypes Resultimentioning
confidence: 94%
“…maternal separation during the entire postnatal period, it was reported that stressed females, but not males had increased infralimbic mPFC apical dendritic branch number and length at PND40 compared to controls (Farrell, Holland, Shansky, & Brenhouse, 2016). Together, these studies suggest that ELS, and in particular LBN, tends to hamper higher order cognitive functions while enhancing the emotional aspects, in particular expression of conditioned fear (Krugers, et al, 2016). …”
Section: Proximal (Neonatal) and Distal (Adult) Phenotypes Resultimentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies show the critical importance of the postnatal period for individual development because stress in this period can have delayed effects on cognition, individual behavior, neuronal plasticity and epigenetics . Nevertheless, the mouse and rat studies on MS and HD effects on cognition in adult females are limited.…”
Section: Discussionmentioning
confidence: 99%
“…In the same line, other authors noted that early maternal rejection predicted increases in child fear and irritability (Lengua, ) and infants of postpartum depressed mothers expressed more negative emotions (Whiffen & Gotlib, ). Parental separation, the quality of parental behavior, childhood trauma, high stress exposure, and abuse may thus be specific vulnerability factors for several mental disorders such as post‐traumatic stress disorder (Pratchett & Yehuda, ), major depressive episodes (Aguilera et al, ; Cai et al, ), anxiety (Krugers et al, ), cognitive impairment (Barzilay et al, ), risk for phobia (Kendler, Neale, Kessler, Heath, & Eaves, ), violent aggression (Mitjans et al, ), and psychotic experiences (Alemany et al, ), among others. The increased risks of personality disorders were particularly characteristic of individuals separated from mothers before the age of five and more prevalent in men (Lahti et al, ), and the development of some of these disorders are mediated by personality organization (Fuchshuber, Hiebler‐Ragger, Kresse, Kapfhammer, & Unterrainer, ).…”
Section: Introductionmentioning
confidence: 99%